A first assessment of the strength of cometary particles collected in-situ by the COSIMA instrument onboard ROSETTA. (15th November 2016) - Hornung, Klaus; Merouane, Sihane; Hilchenbach, Martin; Langevin, Yves; Mellado, Eva Maria; Della Corte, Vincenzo; Kissel, Jochen; Engrand, Cecile; Schulz, Rita; Ryno, Jouni; Silen, Johan; the COSIMA team,
Abstract: Soon after the arrival of the ROSETTA spacecraft at Comet 67/P Churyumov-Gerasimenko the onboard instrument COSIMA ("Cometary Secondary Ion Mass Analyzer") collected a large number of cometary dust particles on targets from gold black of thickness between 10 and 30 μm. Inspection by its camera subsystem revealed that many of them consist of smaller units of typically some tens of micrometers in size. The collection process left the smaller dust particles in an essentially unaltered state whereas most particles larger than about 100 μm got fragmented into smaller pieces. Using the observed fragment size distributions, the present paper includes a first assessment of the strength for those dust particles that were disrupted upon impact. Graphical abstract: Highlights: We collected dust in the near coma of Comet 67P/Churyumov-Gerasimenko. Dust particles fragment upon impact on our collection plates already at speeds of a few m/s. The dust seems to consist of elements of a few tens of micrometers in size which are loosely bound together. An order of magnitude for the strength is derived ( ≈ 10 3 Pa for fragmenting dust of few hundred micrometers size).